2022
DOI: 10.1101/2022.07.16.22277601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 oral tablet vaccination induces neutralizing mucosal IgA in a phase 1 open label trial

Abstract: BackgroundDespite the plethora of efficacious vaccines to the initial Wuhan strain of SARS-CoV-2, these do not induce robust mucosal immunity, offering limited protection against breakthrough infection and replication in the respiratory tract. The mucosa is the first line of defense, therefore a vaccine that induces a mucosal IgA response could be an important strategy in curbing the global pandemic.MethodsWe conducted a single-site, dose-ranging, open-label clinical trial of an oral SARS-CoV-2 vaccine to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For example, Flumist, is more effective in young children than in older adults [30]. More consistent results were observed when the adenovirus bypassed the upper respiratory tract and was delivered by aerosol [31] or by oral delivery in the intestine [17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Flumist, is more effective in young children than in older adults [30]. More consistent results were observed when the adenovirus bypassed the upper respiratory tract and was delivered by aerosol [31] or by oral delivery in the intestine [17].…”
Section: Discussionmentioning
confidence: 97%
“…This temperature stable rAd5 oral vaccine has been administered to over 500 human subjects, has an excellent safety profile, is well tolerated, and generates robust humoral and cellular immune responses against targeted antigens [14][15][16]. In humans, mucosal responses have been shown to be induced in the intestine and the nose following oral tablet delivery [14,17]. Furthermore, the potency of this mucosal immunization strategy has been demonstrated in an aerosol preclinical hamster SARS-CoV-2 transmission study, where unvaccinated hamsters were protected from disease when co-housed with hamsters that were challenged with virus after mucosal immunization [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a single-site, dose-ranging, open-label phase 1 trial of the VXA-CoV-2-1 oral tablet was administered to healthy volunteers aged 18–54 years old (NCT04563702). The results have shown that two oral vaccinations of VXA-CoV-2-1 elicited mucosal secretory IgA in the majority of vaccine recipients, which was highly cross-reactive to variants and persisted for up to 360 days 94 . A phase II clinical trial for dose and age escalation is currently ongoing to evaluate the safety and immunogenicity of VXA-Cov2-1 (NCT 05067933).…”
Section: Currently Available Covid-19 Vaccine Platformsmentioning
confidence: 95%
“…Mucosal immunity was stimulated by the oral tablet vaccine VXA-CoV2–1 (Vaxart) in a Phase 1 trial involving 35 healthy adults. 2 The vaccine, which comprises a non-replicating adenoviral vector expressing the spike and nucleocapsid antigens with a double-stranded RNA adjuvant, elicited IgA antibodies reactive against multiple coronaviruses and persistent for at least one year.…”
Section: Fourth Covid-19 Vaccine Approved In Usmentioning
confidence: 99%